Tinosporae radix: A Review of Traditional Use, Botany, Phytochemistry, Bioactivity, and Quality Marker - Jia, Xiaotong; Ma, Xiaogen; Liu, Pengfei (Combinatorial Chemistry & High Throughput Screening, 2024)
Background: Tinosporae radix is the root tuber of Tinospora capillipes Gagnep of the Menispermaceae family. It has the effects of clearing away heat and toxins, benefiting the throat, relieving pain, and treating sore throat, carbuncle and boils, and other diseases in clinical practice. Methods: The related references about T. radix in this review were collected by online databases, including PubMed, Elsevier, Web of Science, Willy, SciFinder, SpringLink, Google Scholar, Baidu Scholar, ACS publications, Scopus, and CNKI. The other information about T. radix was acquired from ancient books and classical works. Results: T. radix is an important medicinal plant with a variety of traditional uses according to the theory of Chinese medicine. Previous studies revealed that T. radix contained a variety of chemical components, including diterpenoids, alkaloids, steroids, cinnamic acid derivatives, and other compounds. Many pharmacological researches have exhibited that T. radix possesses various biological activities, including anti-cancer, hypoglycemic, anti-inflammatory, anti-bacterial, anti-ulcer, and anti-oxidant activities. Furthermore, the quality markers of T. radix were summarized and analyzed in this paper. Conclusion: The traditional use, botany, phytochemistry, bioactivity, and quality markers of T. radix were reviewed in this paper. It will not only provide an important clue for further studying T. radix, but also supply an important theoretical basis and a valuable reference for in-depth research and exploitations of this plant in the future.
Keywords: bioactivity